FATALITIES IN WILDLAND FIRES FROM 1945 TO 2015 IN SARDINIA (ITALY) - Adrián Cardil (CERNE, 2017)
The worst outcome of wildland res is the loss of human lives, a recurrent phenomenon over the last few decades in Sardinia, Europe and worldwide. This work analyzes all recorded fatalities in wildland res in Sardinia from 1945 to 2015 and trends in terms of annual number of fatalities. This time period was split due to legal and socioeconomic changes periods (1945-1975; 1976-2000; 2001-2015). We classied accident types during wildland res to study the most frequent causes of fatalities and how they were related 1) to involved human groups (professional reghters, auxiliary reghters, and civilians, 2) to re size and 3) to extreme weather conditions. We observed that the annual number of victims was higher in the 1981-1999 period than in other periods with 2.6 fatalities per year. Entrapment is the most frequent cause of death within the re professional reghters (75.6 %). The rate of fatalities seemed to be higher in the 1981- 1999 period for “civilians” and lower for “professional reghters”. We detected that the annual number of “civilian” fatalities is higher in the 1981-1999 period with 1.6 fatalities per year. The calculated rate for “army forces & volunteer reghters” group was in the middle ground. Entrapment is the most frequent cause of death with a percentage of 75.6 %. Fire size is a key factor in the fatality occurrence because over 80 % of deaths in wildland res (without considering aerial accidents) happened in res larger than 100 ha. Days with extreme weather conditions (high temperature or strong winds) were also instrumental because at least 47% of entrapments occurred in this kind of days.